Japanese art - Stanley-Baker, Joan. (London : Thames and Hudson, 1984)
Surveys the arts of Japan from the prehistoric period through the late twentieth century and discusses how it has been influenced by changes in Japan's culture.
Includes bibliographical references (p. 203-205) and index.
Adult
Keywords: Art, Japanese; Japanese art